2011
DOI: 10.1186/cc10543
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver stiffness denotes hepatic dysfunction and mortality risk in critically ill non-cirrhotic patients at a medical ICU

Abstract: IntroductionHepatic dysfunction is a common finding in critically ill patients on the ICU and directly influences survival. Liver stiffness can be measured by the novel method of transient elastography (fibroscan) and is closely associated with hepatic fibrosis in patients with chronic liver disease, but also is increased in patients with acute hepatitis, acute liver failure and cholestasis. We investigated liver stiffness as a potentially useful tool for early detection of patients with hepatic deterioration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 33 publications
(61 reference statements)
1
42
0
Order By: Relevance
“…20 These findings reflect the limited feasibility of TE in patients with severe systemic disorders. 28 The use of the XL-probe may partially overcome this problem especially in cases with obesity, 21 but potential discordance between M-and XL-probes results remains an unsolved problem of this technique and may have impaired diagnostic accuracy in our study as well. 30 In contrast to TE, ARFI values of the right liver lobe did not show any diagnostic value, which may be explained by the smaller amount of tissue volume assessed by ARFI compared with TE.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…20 These findings reflect the limited feasibility of TE in patients with severe systemic disorders. 28 The use of the XL-probe may partially overcome this problem especially in cases with obesity, 21 but potential discordance between M-and XL-probes results remains an unsolved problem of this technique and may have impaired diagnostic accuracy in our study as well. 30 In contrast to TE, ARFI values of the right liver lobe did not show any diagnostic value, which may be explained by the smaller amount of tissue volume assessed by ARFI compared with TE.…”
Section: Discussionmentioning
confidence: 81%
“…8,9,26,27 These findings correspond with data of increased liver stiffness in critically ill non-cirrhotic patients. 28 Beyond that, TE could discriminate selected cases with severe complications in the later post-transplant course probably by reflecting severe acute hepatic injury in cases with liver affection 29 and cardiopulmonary distress in those without hepatic involvement. 26,28 These results are in line with previous case series that reported elevated LSM in patients with acute liver disease in the absence of advanced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In decompensated cirrhotics, VTq shear velocities show a high level of correlation with widely used clinical prognostic scoring systems such as MELD, Child Pugh and Maddrey,35 36 and LSM by TE has shown correlation with a range of liver outcomes and also mortality or need for transplantation 34 37. Interestingly, a further study showed that in a cohort of ICU patients higher LSMs on admission was correlated with a significantly greater risk of mortality, even in those without liver disease 38. This raises the possibility of a wider significance of LSM in the critically ill, including situations beyond primary liver disease.…”
Section: Introductionmentioning
confidence: 96%
“…Liver biopsy is an invasive procedure that is unlikely to become a routine part of the pre-transplant evaluation. Novel imaging strategies to assess fibrosis, including transient elastography and diffusionweighted magnetic resonance imaging, have been validated in critically ill non-cardiac patients 16 and may help to risk stratify patients with severe heart failure. Likewise, novel biomarkers of hepatic fibrosis and apoptosis, including fibroblast growth factor-23, Toll-like receptor 4, and epitopes of hepatic cytokeratin-18, 17-19 may help target appropriate candidates for liver biopsy.…”
mentioning
confidence: 99%